KARAKTERISTIK FISIKOKIMIA VIRGIN COCONUT OIL DALAM BERAGAM KONSENTRASI ASAM ASETAT DAN WAKTU INKUBASI - Parwiyanti Parwiyanti; Eka Lidiasari; Bambang Yudono; Tyas Dwi Wijayanti (BPFP Faperta UNIB, 2023)
Virgin Coconut Oil (VCO) is a processed coconut product that has the potential to be used as a raw material for cosmetics and medicine. The purpose of this research is to determine the concentration of acetic acid and incubation time that give the best physicochemical characteristics of VCO. The research design used a Completely Randomized Factorial Design (CRFD) with two treatment factors, each repeated three times. The first treatment factor was the concentration of acetic acid (1%, 1.5%, 2%, and 2.5%), and the second factor was the incubation time (24 hours, 48 hours, and 72 hours). The parameters observed were pH, yield, free fatty acid content, moisture content, and clarity degree. The results showed that the concentration of acetic acid and incubation time had a significant effect on the yield. The interaction of the two treatment factors had a significant effect on the pH, yield, free fatty acid content, moisture content, and clarity degree. The best treatment was obtained at a concentration of 1% acetic acid and an incubation time of 24 hours, resulting in a yield of 16.3%, moisture content of 0.07%, and clarity degree of 95.56%, which met the quality requirements for VCO except for the free fatty acid content (1.71%).